EKSISTENSI SENI ORMATAN TARAWANGSA: FUNGSI TARAWANGSA DI TENGAH EKOSISTEM MASYARAKAT BANJARAN - Suryaman, Atang; Masyuning, Masyuning; Herizal, Maspon (Paraguna, 2023)
The existence of Tarawangsa Cangkungan, which is still alive and continues to grow, cannot be separated from its existence which is still functioned in many contexts, such as hajat overtime, ngaruat, and treating the sick. In the context of the ecosystem, the study in this paper takes focus and limits. The times have become one of the factors contributing to the loss of traditional culture and arts. Therefore, the continuity of an art cannot be separated from how the artists maintain and continue the tradition. The art of tarawangsa Banjaran is an example of a case where this art was once alive and well known in the community, but due to the lack of regeneration efforts and the decreasing number of artists who continue it, this art has finally experienced a period of vacuum and is now almost extinct. So far, one of the main problems has been the strict restrictions on the regeneration process of Banjaran's tarawangsa art. This policy requires prospective heirs to have blood ties to the previous presenting artist as the main requirement. This condition has become a barrier for the younger generation who are interested in learning this art.